Mechanisms of sustained long-term weight loss after RYGB: α-MSH is a key factor. (June 2018) - Farias, Gisele; Netto, Bárbara Dal Molin; Boritza, Katia Cristina; Bettini, Solange Cravo; Dâmaso, Ana Raimunda; de Freitas, Alexandre Coutinho Teixeira
Highlights: Leptin, α-MSH and PYY has an intrinsic action stimulating the anorexigenic pathways in a post RYGB. Anorexigenic pathways may play a prominent role in the effectiveness of the RYGB. The central melanocortin system may be a key role in sustained long-term weight loss. α-MSH contributes to weight loss by stimulate lipolysis and adipose tissue browning. Compensatory hormonal adaptation leads to increased appetite favoring weight regain.